1981
DOI: 10.1139/v81-305
|View full text |Cite
|
Sign up to set email alerts
|

Protonated cyclopropanes in α-aminoketone deamination

Abstract: . Can. J. Chem. 59,2096Chem. 59, (1981. Deamination of 2-amino-4,4-dideuterio-6,6-dimethylcyclohexanone, 2-exo-amino-and 2-endo-amino-norbornane-3-one, 2-diazonorbornan-3-one, 2-exo-amino-5,6-exo-dideuterionorbornan-3-one and the corresponding 5,6-endo-dideuterio isomer has been studied. The nature of the products, the deuterium location in them, and the high retention of steric identity in the carbocations are interpreted in terms of o-bond participation leading to corner-and edge-protonated cyclopropanes as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…a 4:1 mixture of a/ß epimers. (7) I support a mechanism which is essentially an acid-catalyzed etherification. The ratio of the epimeric products (a and ß anomers) produced (as estimated by NMR) depends largely on the aglycon used and reflects the net effect of two counteracting properties: (a) aglycon nucleophilicity and (b) its tendency to form a stabilized carbocation resulting from a formal loss of an -OH group.…”
Section: Resultsmentioning
confidence: 78%
“…a 4:1 mixture of a/ß epimers. (7) I support a mechanism which is essentially an acid-catalyzed etherification. The ratio of the epimeric products (a and ß anomers) produced (as estimated by NMR) depends largely on the aglycon used and reflects the net effect of two counteracting properties: (a) aglycon nucleophilicity and (b) its tendency to form a stabilized carbocation resulting from a formal loss of an -OH group.…”
Section: Resultsmentioning
confidence: 78%
“…Its ESIMS showed a quasimolecular ion peak at m/z 388 [Mþ1] þ and its NMR spectroscopic patterns are quite different from those of its starting material 2. The NMR ( 1 H, 13 (Fig. 1), which indicated that the vicinal glycol moiety in 2 had undergone Pinacol rearrangement.…”
Section: Resultsmentioning
confidence: 98%
“…Melting points were determined on a Kofler block (uncorrected); optical rotations were measured in a 1.0 dm cell with a PE-314 polarimeter at 20AE1 C; IR spectra were recorded on a Nicolet 200 SXV spectrometer; MS spectra were obtained with Finnigan LCQ DECA mass spectrometer; HRMS spectra were obtained with a Bruker BioTOFQ mass spectrometer; 1 H and 13 , and the mixture was stirred at 0 C for 1.5 h prior to be quenched with saturated Na 2 SO 3 . The organic layer was separated and the aqueous layer was re-extracted with CH 2 Cl 2 (15 mlÂ2).…”
Section: General Methodsmentioning
confidence: 99%
“…This was prepared by the action of acid on bryodulcosigcnin (16) from Brqo~~icr crlhcr (20). After crystallization from acctone-liexanc it had mp 157-158°C.…”
Section: B~y O G O~~i~r (1 7)mentioning
confidence: 99%
“…Final proof of structure of A and B came from interrelation with the cucurbitacins bryodulcosigenin 16 (20) and bryogenin 17 ( 19) from Bryorzia alba (20) .' The 24-carbony l of bryogenin was removed in two ways, by cyanoborohydride reduction (21) of its 24-tosylhydrazone (18) or by Wolff-Kishner reduction of the 24-semicarbazone.…”
mentioning
confidence: 99%